2023
DOI: 10.1111/1365-2656.14000
|View full text |Cite
|
Sign up to set email alerts
|

Linking physiology and climate to infer species distributions in Australian skinks

Rodolfo O. Anderson,
Reid Tingley,
Conrad J. Hoskin
et al.

Abstract: Climate has a key impact on animal physiology, which in turn can have a profound influence on geographic distributions. Yet, the mechanisms linking climate, physiology and distribution are not fully resolved. Using an integrative framework, we tested the predictions of the climatic variability hypothesis (CVH), which states that species with broader distributions have broader physiological tolerance than range‐restricted species, in a group of Lampropholis skinks (8 species, 196 individuals) along a latitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Fifteen minutes before each performance measure, lizards were placed in an incubator at 28 °C to ensure constant body temperature across lizards. Although recent studies have shown that the thermal optimum is slightly higher than 28 °C ( Anderson et al 2023 ; Zhang et al 2023 ) there is substantial individual and species-specific variation with 28 °C being firmly within this range. Animals were then transferred to the racetrack and were chased down toward a terrarium placed at the end of the track.…”
Section: Methodsmentioning
confidence: 96%
“…Fifteen minutes before each performance measure, lizards were placed in an incubator at 28 °C to ensure constant body temperature across lizards. Although recent studies have shown that the thermal optimum is slightly higher than 28 °C ( Anderson et al 2023 ; Zhang et al 2023 ) there is substantial individual and species-specific variation with 28 °C being firmly within this range. Animals were then transferred to the racetrack and were chased down toward a terrarium placed at the end of the track.…”
Section: Methodsmentioning
confidence: 96%